Comparative Analysis Between Strip and Gels Indicated for at Home Bleaching: Analysis of Color Alteration, Roughness and Microhardness of Dental Enamel - Aidar, K. M.S. [UNESP]; Cintra, Luciano Tavares Angelo [UNESP]; Ferreira, M. C.B. [UNESP]; Fagundes, Ticiane Cestari [UNESP]; Esteves, L. M.B. [UNESP]; Goto, J. [UNESP]; Catelan, Anderson [UNESP]; Briso, André Luiz Fraga [UNESP] (Wiley, 2025)
Purpose: To compare the color alteration, surface roughness and microhardness and cross-sectional microhardness of bovine enamel treated with at-home whitening strips and gels. Materials and Methods: Sixty-six pigmented specimens (n = 11) were allocated to six groups: C—cotton wool moistened with distilled water for 1 h; SDS—sodium dithionite strip, for 1 h; HPS—6.5% hydrogen peroxide strip, for 1 h; CPS—20% carbamide peroxide strip, for 1 h; HPG—7.5% hydrogen peroxide gel, for 1 h; CPG—10% carbamide peroxide gel, for 4 h. The treatments lasted 10 days, calculating the ∆E, ∆E00, and ∆WID at baseline, 5 and 10 days, and 14 days after completion. Additional 66 polished discs (n = 11) were used to analyze the surface roughness and microhardness of enamel before and after bleaching, cross-sectional microhardness and integrated mineral loss (ΔZ; %Vol × μm). Data were subjected to statistical analysis by two-way Anova RM and Tukey post-test (α = 0.05). Results: In ∆E and ∆WID analysis, greater values were obtained in CPG (p < 0.001), followed by HPG and HPS (p = 0.271). SDS and CPS (p < 0.001) exceeded only C (p < 0.001). In ∆E00, at completion of treatments, the results were similar; however, HPG = HPS = CPS (p = 0.237). There was an increase in roughness and decrease in surface microhardness in all bleaching groups (p < 0.005). Concerning the cross-sectional microhardness, the treatments were equal to C at 150 μm, the last depth analyzed. For ΔZ, the values of SDS, CPS, HPG, and CPG groups showed similar mineral loss (p > 0.001), and the lowest value was exhibited in the Control group, followed by HPS group (p < 0.001). Conclusion: Although the strips were aesthetically effective, the CPG and HPG groups presented highest values in the ∆E00 and ∆WID analysis. However, all treatments influenced the enamel surface, increasing roughness and decreasing surface and transverse microhardness. Clinical Relevance: The whitening gels promoted greater chromatic changes, but all treatments affected the enamel surface, increasing roughness and decreasing surface and transverse microhardness.
Keywords: carbamide peroxide; dentistry; hydrogen peroxide; tooth whitening